OPTIMALISASI PENDAPATAN KELUARGA DI ERA NEW NORMAL PADA UKM SEDAYU PUTRI DI DUSUN LOKON RANGAN KECAMATAN KAYANGAN KABUPATEN LOMBOK UTARA - Sulaimiah, Sulaimiah; Sulhaini, Sulhaini; Nururly, Santi (Lafadz Jaya Publisher, 2023)
The community service carried out at the Sedayu Putri Micro Small Business in Lokon Rangan Hamlet, Kayangan District, North Lombok Regency is to increase the community's ability to manage the potential of the surrounding villages, especially from fishery products, namely fish processing with various flavors and aromas that can attract interest. not from the lower economic class but also targeting sales to the upper economic class as the main food and snack for the community around the service location, even those outside the area can enjoy it. Starting from production by looking for quality input materials, then the production process is handled by skilled employees and attractive packaging. The potential of this village is very large, and it needs a good touch to be able to produce quality products that are superior to its competitors. In this service, counseling is given about production and workforce development so that they have skills according to needs, namely having a good entrepreneurial spirit, diligently working and paying attention to the quality of the production produced.